Haptics: Generating and Perceiving Tangible Sensations International Conference, EuroHaptics 2010, Amsterdam, July 8-10, 2010. Proceedings, Part I - Kappers, Astrid M. L.; Erp, Jan B. F.; Bergmann Tiest, Wouter M.; Helm, Frans C. T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the conference on Haptics: Generating and Perceiving Tangible Sensations, held in Amsterdam, Netherlands in July 2010.
Mass, Force, and Elasticity -- Efficient Bimodal Haptic Weight Actuation -- The Contribution of Proprioceptive and Cutaneous Cues in Weight Perception: Early Evidence for Maximum-Likelihood Integration -- The Shape-Weight Illusion -- Force-Based Calibration of a Particle System for Realistic Simulation of Nonlinear and Viscoelastic Soft Tissue Behavior -- Haptic Perception of Viscosity -- Multi-sensorial Interface for 3D Teleoperations at Micro and Nanoscale -- Classifying Torque, Normal Force and Direction Using Monkey Afferent Nerve Spike Rates -- A New Coupling Scheme for Haptic Rendering of Rigid Bodies Interactions Based on a Haptic Sub-world Using a Contact Graph -- A New Multi-DOF Haptic Device Using a Redundant Parallel Mechanism -- Estimation of Normal and Tangential Manipulation Forces by Using Contact Force Sensors -- Modeling and Experimental Studies of a Novel 6-DOF Haptic Device -- Inertial Force Display to Represent Content Inside the Box -- Perception of Stiffness during Interaction with Delay-Like Nonlinear Force Field -- Improving the Prediction of Haptic Impression User Ratings Using Perception-Based Weighting Methods: Experimental Evaluation -- Vibrotactile Force Perception Thresholds at the Fingertip -- Optimum Design of 6R Passive Haptic Robotic Arm for Implant Surgery -- Creating Virtual Stiffness by Modifying Force Profile of Base Object -- Extended Rate-Hardness: A Measure for Perceived Hardness -- Using a Fingertip Tactile Device to Substitute Kinesthetic Feedback in Haptic Interaction -- The Effect of Bimanual Lifting on Grip Force and Weight Perception -- How to Build an Inexpensive 5-DOF Haptic Device Using Two Novint Falcons -- Revisiting the Effect of Velocity on Human Force Control -- Teleoperation -- A Coordinating Controller for Improved Task Performance in Multi-user Teleoperation -- Mechatronic Design Optimization of a Teleoperation System Based on Bounded Environment Passivity -- On the Impact of Haptic Data Reduction and Feedback Modality on Quality and Task Performance in a Telepresence and Teleaction System -- Stability Analysis of Mobile Robot Teleoperation with Variable Force Feedback Gain -- Transparency of the Generalized Scattering Transformation for Haptic Telepresence -- VerroTouch: High-Frequency Acceleration Feedback for Telerobotic Surgery -- A Turing-Like Handshake Test for Motor Intelligence -- The Influence of Different Haptic Environments on Time Delay Discrimination in Force Feedback -- Perception and Action in Simulated Telesurgery -- Parallel Kinematics for Haptic Feedback in Three Degrees of Freedom: Application in a Handheld Laparoscopic Telemanipulation System -- Mechanical Impedance: A Cobotic and Haptic Actuators Performance Criterion -- Online Intention Recognition in Computer-Assisted Teleoperation Systems -- Evaluation of a Coordinating Controller for Improved Task Performance in Multi-user Teleoperation -- Effects of Force Feedback and Arm Compliance on Teleoperation for a Hygiene Task -- Telepresence Technology for Production: From Manual to Automated Assembly -- High Fidelity Haptic Rendering for Deformable Objects Undergoing Topology Changes -- Novel Approaches -- Basic Properties of Phantom Sensation for Practical Haptic Applications -- Evaluation of Transmission System for Spatially Distributed Tactile Information -- Electro-tactile Display with Real-Time Impedance Feedback -- Life Log System Based on Tactile Sound -- What Is It Like to Be a Rat? Sensory Augmentation Study -- Innovative Real-Time Communication System with Rich Emotional and Haptic Channels -- Tactile vs Graphical Authentication -- Haptics Can (3z(BLend a Hand(3y (Bto a Bionic Eye -- Analysis of Active Handrest Control Methods -- Roly-poly: A Haptic Interface with a Self-righting Feature -- HaptiHug: A Novel Haptic Display for Communication of Hug over a Distance -- Physical Contact of Devices: Utilization of Beats for Interpersonal Communication -- Tremor Suppression Control for a Meal-Assist Robot -- Reflective Haptics: Enhancing Stylus-Based Interactions on Touch Screens -- A Novel Tactile Sensor for Detecting Lumps in Breast Tissue -- Tactile Sensation Imaging for Artificial Palpation -- Improving Vehicular Window Control with Haptic and Visual Feedback -- Gesture Recognition in the Haptic Creature.s
Keywords: Computer science; Software engineering; Information systems; Artificial intelligence; Computer simulation; Computer Science; User Interfaces and Human Computer Interaction; Simulation and Modeling; Special Purpose and Application-Based Systems; Information Systems Applications (incl.Internet).; Computers and Society; Artificial Intelligence (incl. Robotics).